(untitled) (Revista de Ciências Agroveterinárias, 2021)
The wood, due to its chemical constitution, is susceptible to biodeteriorating agents, especially when exposed to adverse conditions, such as in contact with the soil. Thus, the present study aimed to evaluate the effect of preservative treatment with Chromated Copper Arsenate (CCA) and the period of exposure to the field on the mechanical resistance of Eucalyptus grandis and Eucalyptus cloeziana wood. For this, trees with 16 years of age, of both species, were used, which were processed in boards and subjected to outdoor drying, to subsequently carry out the preservative treatment in an autoclave with CCA. From the treated boards, samples of 2.0 x 2.0 x 30.0 cm were made, which were installed in rotting fields in two different areas, open field and forest, in the city of Santa Maria/RS. Periodically, samples were collected to evaluate their degradation over of exposure period, which were subjected to mechanical static bending testing. Based on the results obtained, it was observed that the preservative treatment had a beneficial effect, maintaining the mechanical resistance of the wood for a longer period of time. The effect was more pronounced for E. cloeziana wood, which naturally already had greater mechanical resistance than E. grandis wood. Thus, it is concluded that the treatment is efficient in reducing the deterioration of wood in the field.